Country Representatives’ Perceptions of the Biodiversity Science-Policy Interface - André Derek Mader; Brian Alan Johnson; Yuki Ohashi; Isabella Fenstermaker (Conservation, 2021)
Biodiversity knowledge is communicated by scientists to policymakers at the biodiversity “science-policy interface” (SPI). Although the biodiversity SPI is the subject of a growing body of literature, gaps in our understanding include the efficacy of mechanisms to bridge the interface, the quality of information exchanged between science and policy, and the inclusivity of stakeholders involved. To improve this understanding, we surveyed an important but under-studied group—biodiversity policymakers and scientific advisors representing their respective countries in negotiations of the Convention on Biological Diversity (CBD) and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). We found that a wide variety of SPI mechanisms were being used. Overall, they were considered to be sufficiently effective, improving over time, and supplied with information of adequate quality. Most respondents, however, agreed that key actors were still missing from the biodiversity SPI.